2023
DOI: 10.3389/fpls.2022.1125003
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of barley ferulate 5-hydroxylase dramatically alters straw lignin structure without impact on mechanical properties

Abstract: Barley is a major cereal crop for temperate climates, and a diploid genetic model for polyploid wheat. Cereal straw biomass is an attractive source of feedstock for green technologies but lignin, a key determinant of feedstock recalcitrance, complicates bio-conversion processes. However, manipulating lignin content to improve the conversion process could negatively affect agronomic traits. An alternative approach is to manipulate lignin composition which influences the physical and chemical properties of straw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
(105 reference statements)
1
8
0
Order By: Relevance
“…The blastp search in the sugarcane genome database S. officinarum x spontaneum R570 v2.1 (Phytozome 13) allowed us to retrieve the top sixteen protein sequences (e-values: 0 - 18e-180), compared to the previously identified 50 , 52 and cloned (KT777465.1) ShF5H. The amino acid (aa) sequences of sugarcane, monocot species, and Arabidopsis, retrieved from the Phytozome and TAIR databases using ShF5H1 as a query (BLASTp), along with the sequences from Shafiei et al, 44 were aligned and used to construct the phylogenetic tree (Figure S3). The CYP84 family comprises cytochrome P450 (CYP) monooxygenase enzymes, as F5H from the lignin pathway.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The blastp search in the sugarcane genome database S. officinarum x spontaneum R570 v2.1 (Phytozome 13) allowed us to retrieve the top sixteen protein sequences (e-values: 0 - 18e-180), compared to the previously identified 50 , 52 and cloned (KT777465.1) ShF5H. The amino acid (aa) sequences of sugarcane, monocot species, and Arabidopsis, retrieved from the Phytozome and TAIR databases using ShF5H1 as a query (BLASTp), along with the sequences from Shafiei et al, 44 were aligned and used to construct the phylogenetic tree (Figure S3). The CYP84 family comprises cytochrome P450 (CYP) monooxygenase enzymes, as F5H from the lignin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The major group is divided into two subgroups: one containing non-characterized proteins, which includes TaF5H2–3, HvF5H4, MsF5H3, SbF5H2, and ShF5H2–4. In contrast, the red-colored subgroup comprises grass proteins that have been functionally characterized (indicated by single asterisks), such as SbF5H1, 43 OsF5H1, 42 HvF5H1, 44 and PvF5H1a, 31 suggesting that the members of this subgroup play a similar role in S-lignin synthesis. Among the sugarcane CYP84A proteins, only one member belongs to the mentioned subgroup, ShF5H1 (indicated by double asterisks), positioned closest to SbF5H, whose overexpression led to an increase in syringyl acid and S units in sorghum.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a serial of work from the transgenic plants, feeding tests, and in vitro biochemistry have demonstrated that F5H actually used coniferaldehyde and coniferyl alcohol to form 5-hydro-coniferaldehyde and 5-hydro-coniferyl alcohol then syringyl alcohol. Over-expressing F5H in transgenic tobacco and poplar gave rise to lignin that was composed of almost S units [ 26 , 27 , 28 ]. Therefore, F5H is now also called coniferaldehyde 5-hydroxylase (CAld-5H) [ 29 ].…”
Section: Unique Features Of Lignin Biosynthesismentioning
confidence: 99%